Which patients are less likely to improve after arthroscopic rotator cuff repair? - Barak Haviv; Tal Frenkel Rutenberg; Lee Yaari; Muhammad Khatib; Ehud Rath; Mustafa Yassin (Acta Orthopaedica et Traumatologica Turcica, 2019)
Objective: The aim of this study was to evaluate which specific factors influence the improvement in function and to estimate the time to obtain pain relief following arthroscopic rotator cuff repair. Methods: A total of 97 patients (57 men and 40 women; mean age: 55.5 ± 9.3 years) who had arthroscopic rotator cuff repair between 2013 and 2016 were included into the study. Multivariable stepwise analysis included preoperative variables (age, gender, body mass index, comorbidities, occupation and participation in sports, Oxford shoulder score at baseline, preceding injury and duration of preoperative symptoms) and arthroscopic findings (size of rotator cuff tear, pathology of the long head of the biceps and cartilage lesions). The change in the Oxford shoulder score at the last follow-up was modeled as a function of the above predictor variables. The time to regain a visual analogue scale (VAS) under two points following surgery was considered the time to regain substantial pain relief. Results: The mean follow-up time was 33.2 ± 14.4 months. Twenty three patients had partial thickness and seventy four had full thickness supraspinatus tears. In third of the patients the tears were defined as large full thickness. At the last follow-up the mean Oxford shoulder score improved from 13.8 ± 4.8 to 42.1 ± 7.2 points (P < 0.001). The mean VAS improved from a preoperative score of 6.7 ± 1.3 points to 1.5 ± 0.6 points postoperatively (P < 0.001) and 80 (83%) patients declared they were satisfied to have had the operation. The mean time interval for substantial pain relief was 4.9 ± 3.6 months. Patients with higher preoperative Oxford shoulder score and larger tear size were correlated with lesser improvement in Oxford shoulder score (R = 0.5, P = 0.001). Conclusion: Arthroscopic rotator cuff repair improved pain and function at an average follow-up of three years. A substantial pain relief was regained within five months from surgery. Larger rotator cuff tear size and more favorable preoperative function were predictors of worse postoperative function. Level of evidence: Level IV, Therapeutic study. Keywords: Shoulder, Rotator cuff repair, Rotator cuff tear, Supraspinatus, Factors, Predictors, Multivariable analysis, Oxford shoulder score